Saraca indica Bark Extract Shows In Vitro Antioxidant, Antibreast Cancer Activity and Does Not Exhibit Toxicological Effects. (16th March 2015) - Yadav, Navneet Kumar; Saini, Karan Singh; Hossain, Zakir; Omer, Ankur; Sharma, Chetan; Gayen, Jiaur R.; Singh, Poonam; Arya, K. R.; Singh, R. K.
Abstract : Medicinal plants are used as a complementary and alternative medicine in treatment of various diseases including cancer worldwide, because of their ease of accessibility and cost effectiveness. Multicomposed mixture of compounds present in a plant extract has synergistic activity, increases the therapeutic potential many folds, compensates toxicity, and increases bioavailability. Saraca indica (family Caesalpiniaceae) is one of the most ancient sacred plants with medicinal properties, exhibiting a number of pharmacological effects. Antioxidant, antibreast cancer activity and toxicological evaluation of Saraca indica bark extract (SIE) were carried out in the present study. The results of the study indicated that this herbal preparation has antioxidant and antibreast cancer activity. Toxicological studies suggest that SIE is safer to use and may have a potential to be used as complementary and alternative medicine for breast cancer therapy.